2019
DOI: 10.1177/0145561319864578
|View full text |Cite
|
Sign up to set email alerts
|

Is Nasal Endoscopy of Diagnostic Value in Chronic Rhinosinusitis Without Nasal Polyps?

Abstract: Endoscopic examination of the nasal cavity is an integral part of the assessment of patients with chronic rhinosinusitis. However, the benefit gained by performing endoscopy with respect to the patient’s medical condition has not been completely assessed. We conducted a prospective cohort in an academic medical center. Thirty-nine patients diagnosed with chronic rhinosinusitis, without polyps, whose ailment was managed conservatively with no surgical intervention. All patients underwent nasal endoscopy, a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…The majority of the included publications (75%) demonstrated a lack of correlation with PROMs. Very weak correlations ( r < 0.35) were found in the remaining 25% publications 18,21–26,34,40,45,68–72,74,91,92 . Of note, the largest‐scale study with 1840 CRS patients showed a clinically insignificant correlation ( r = 0.058).…”
Section: Resultsmentioning
confidence: 96%
“…The majority of the included publications (75%) demonstrated a lack of correlation with PROMs. Very weak correlations ( r < 0.35) were found in the remaining 25% publications 18,21–26,34,40,45,68–72,74,91,92 . Of note, the largest‐scale study with 1840 CRS patients showed a clinically insignificant correlation ( r = 0.058).…”
Section: Resultsmentioning
confidence: 96%
“…Експериментальний риносинусит у кролів був індукований у 1-й день дослідження шляхом тампонади правої половини носової порожнини під загальною анестезією (кетамін/ксилазин -35/5 мг/кг, внутрішньом'язово) [21], що є добре відомою моделлю риносинуситу (РС) в експериментальній ринології [22,23]. Через 15 діб після відтворення патології у кролів вилучали тампони та проводили контроль наявності РС за допомогою назальної ендоскопії [24][25][26]. Також здійснювали забір крові з вушної вени і вивчали гематологічні показники стандартними лабораторними методами [27][28][29].…”
unclassified